2000
DOI: 10.1038/sj.onc.1203309
|View full text |Cite
|
Sign up to set email alerts
|

The APC-hDLG complex negatively regulates cell cycle progression from the G0/G1 to S phase

Abstract: The adenomatous polyposis coli (APC) gene is mutated in familial adenomatous polyposis and in many sporadic colorectal tumors. The carboxyl-terminal S/TXV motif of the APC gene product interacts with the PDZ domain of hDLG, the human homolog of the Drosophila lethal (1) discs large-1 (dlg) tumor suppressor. In the present study, we found that overexpression of hDLG suppresses cell proliferation by blocking cell cycle progression from the G0/G1 to S phase. This inhibition of cell cycle progression was abolished… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
173
2
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(180 citation statements)
references
References 36 publications
3
173
2
1
Order By: Relevance
“…hDlg is the human homologue of the Drosophila tumor suppressor gene Dlg and has been suggested to have a negative role in cell proliferation (Ishidate et al, 2000;Humbert et al, 2003). In the present study, we have shown that TEM5 directly binds to the PDZ domains of hDlg via its C-terminal four aa, and that TEM5 colocalizes with hDlg in endothelial cells of mouse embryonic liver.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…hDlg is the human homologue of the Drosophila tumor suppressor gene Dlg and has been suggested to have a negative role in cell proliferation (Ishidate et al, 2000;Humbert et al, 2003). In the present study, we have shown that TEM5 directly binds to the PDZ domains of hDlg via its C-terminal four aa, and that TEM5 colocalizes with hDlg in endothelial cells of mouse embryonic liver.…”
Section: Discussionmentioning
confidence: 55%
“…The PDZ domains of hDlg interact with tumor suppressor proteins, adenomatous polyposis coli (APC) and protein tyrosine phosphatase and tensin homologue (PTEN), and several viral oncoproteins such as the E6 protein of oncogenic human papillomavirus (Humbert et al, 2003). It has been reported that overexpression of hDlg in fibroblasts leads to an impaired G1-S phase progression and inhibition of cell proliferation (Ishidate et al, 2000). Thus, hDlg, like Dlg, is likely to be involved in the negative regulation of cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its modular organization, PTP-BL may build up a multiprotein complex recruiting the APC protein within the nucleus, which may be involved in cell cycle regulation. Thus, overexpression of the APC protein blocks the progression from G0 Ā± G1 to the S phase of the cell cycle Ishidate et al, 2000) and the capability of the APC protein to interact directly with DNA was demonstrated recently (Deka et al, 1999). Although these data suggest an involvement of the APC protein in cell division, the intracellular signaling cascades involved in APC function remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…A human homologue of Dlg, HDLG, binds directly to the 4.1 protein and to the product of the APC tumor suppressor gene (Lue et al, 1994;Matsumine et al, 1996). The later complex negatively regulates progression of the cell cycle from G0/G1 to S phase (Ishidate et al, 2000). The Lgl protein is bound to the inner surface of lateral cell membranes in regions of cell junctions, and it is present in high molecular weight aggregates (Strand et al, 1994a,b).…”
Section: Introductionmentioning
confidence: 99%